A Comprehensive Review of Commonly used Taila Yogas in the Management of Vatavyadhi - Joshi, Aishwarya; P, Seethadevi (Journal of Neonatal Surgery, 2025)
Vatavyadhi, a group of disorders rooted in the vitiation of Vata dosha, is characterized by diverse clinical manifestations such as pain, stiffness, tremors, and neurological deficits. According to Ayurveda, Taila (medicated oil) is a prime therapeutic agent for pacifying Vata due to its snigdha (unctuous), ushna (hot), and sukshma (penetrating) qualities. Taila yogas are widely used in both internal (abhyantara) and external (bahya) therapies such as Abhyanga, Basti, Snehapana, and Nasya. Classical texts enumerate numerous Taila preparations, each tailored to specific pathophysiological states of Vata disorders. However, there is a need for a systematic exploration of their pharmacodynamics, therapeutic indications, and clinical outcomes. Aim: To conduct a comprehensive analysis of Taila yogas used in the management of Vatavyadhi with reference to their classical formulations, Taila Murcchana, Concept of Avartana therapeutic roles and modes of administration. Materials and Methods: A textual review of Ayurvedic classical texts (Charaka Samhita, Sushruta Samhita, Ashtanga Hridaya, and others) was undertaken to identify and categorize various Taila yogas indicated for Vatavyadhi. The Tailas were analyzed on the basis of their composition (dravya content), guna-karma (properties and actions), route of administration, and their applicability in Vatavyadh is such as Pakshaghata, Gridhrasi, Katigraha, and Sandhivata. Results: Taila formulations were identified with specific utility in different forms of Vatavyadhi. Conclusion: Taila yogas offer a time-tested, holistic approach to managing Vatavyadhi, addressing both symptomatic relief and disease pathology. Their proper selection, based on dosha, dushya, and disease stage, enhances therapeutic efficacy. The analysis highlights the rationale behind ingredient selection, method of preparation (Sneha Paka Vidhi), and mode of application including Abhyanga, Basti, and Nasya and Pana.